(untitled) (Applied Biological Research, 2014)
Sixty non-pregnant and non-lactating adult women in the age group of 25-35 years from the farm families (land holdings between 2-4 ha) were purposively selected from village Ayali Kalan, district Ludhiana, Punjab (India) to assess their food and nutrient intake in the context of iron deficiency anemia. Forty percent of the subjects had their hemoglobin tested and only 3% reported deworming treatment in the last one year. The mean hemoglobin was 10.5 ± 1.18 g dL-1. Eighty three percent of the subjects were anemic out of which 13 and 70% were mildly and moderately anemic. The overall adequacy of cereals, pulses, green leafy vegetables, roots and tubers, fruits, other vegetables, milk and milk products, sugars and fats & oils in the diets of farm women was 98, 54, 5, 63, 49, 16, 122, 141 and 216%, respectively. Of the 7 nutrients studied, calcium was found adequate while energy, protein, folate, ascorbic acid and iron were marginally adequate with nutrient adequacy ratios of 75- 100%. Only β-carotene was marginally inadequate. The mean adequacy ratio was 83% which gives satisfactory picture of nutritional intake of the farm women. Though the intake of most of the nutrients related to iron nutriture of farm women were marginally adequate, the hematological profile, as revealed by the hemoglobin levels in subjects, showed dismal condition of their iron status.